Effects of stocking density on the growth performance, mitophagy, endocytosis and metabolism of Cherax quadricarinatus in integrated rice–crayfish farming systems - Dong, Yin; Jia, Rui; Hou, Yiran; Diao, Weixu; Li, Bing; Zhu, Jian (Frontiers in Physiology, 2022)
Red claw crayfish (Cherax quadricarinatus) is an economic freshwater shrimp with great commercial potential. However, the suitable stocking density of C. quadricarinatus is still unclear in integrated rice–crayfish farming system. Thus, this study aimed to investigate the effects of stocking density on growth performance, mitophagy, endocytosis and metabolism of C. quadricarinatus. The C. quadricarinatus was reared at low density (LD, 35.73 g/m2), middle density (MD, 71.46 g/m2) and high density (HD, 107.19 g/m2) in an integrated rice–crayfish farming system. After 90 days of farming, the growth performance of C. quadricarinatus significantly decreased in the MD and HD groups relative to that in the LD group. The HD treatment caused oxidative stress and lipid peroxidation at the end of the experiment in hepatopancreas. Transcriptome analysis showed that there were 1531 DEGs (different expression genes) between the LD group and HD group, including 1028 upregulated genes and 503 downregulated genes. KEGG (Kyoto Encyclopedia of Genes and Genomes) enrichment analysis indicated that the DEGs were significantly enriched in endocytosis and mitophagy pathways. Meanwhile, four lipid metabolism pathways, including biosynthesis of unsaturated fatty acids, fatty acid biosynthesis, glycerolipid metabolism and glycerophospholipid metabolism, exhibited an upregulated tendency in the HD group. In conclusion, our data showed that when the stocking density reached up to 207.15 g/m2 in HD group, the growth performance of C. quadricarinatus was significantly inhibited in this system. Meanwhile, the data indicated that C. quadricarinatus may respond to the stressful condition via activating antioxidant defense system, endocytosis, mitophagy and metabolism-related pathways in hepatopancreas.